(3GdefXeI GdOhdjI ddJhMjO GdbjGSj (B:s (3GdGjRh (B9000 - 2000 /s - (3MehO, NVjQ cGXes ((3YeGf(B: s (3OGQ UaGA(B, s, 2010)
(3eaghe EOGQI GdLhOI GdTGedI h eaghe h CgejI GdEjRh (B2000-9000 (3h SdSdI GdehGUaGJ h GdebGjjS (Biso 9000 (3GdEjRh h GOGQI GdLhOI GdTGedI h eJWdHGJ fXGe GdLhOI GdGjRh (B9000(3h JfajP fXGe GdLhOI h JWHjb eJWdHGJg h GdCSS GdYedjI dJWHjb fXGe GdEjRh h gjcdI GdJhKjb h CNjQG GdJSLjds
Keywords: (3GdEjRhs; (3VHW GdLhOIs; (3efXeGJ GdJbjjS GdOhdjIs